2016
DOI: 10.1021/acs.chemmater.6b00049
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electronic Structure and Surface Defects in Chromium-Doped Colloidal SrTiO3−δ Nanocrystals

Abstract: Materials. Oleic acid (90%, Fisher Chemical), titanium(IV) bis(ammonium lactate)dihydroxide (TiALH, 50% wt in water * , Alfa Aesar), Sr(OH) 2 •8H 2 O (99%, Alfa Aesar), Cr(NO 3 ) 3 •9H 2 O (Crystalline Certified, Fisher Chemical), tetramethylammonium hydroxide (10 M NMe 4 OH, Acros Organics), hydrazine hydrate (N 2 H 4 •H 2 O, 99%, Acros Organics), ethanol (200 proof, PHARMCO-AAPER) and hexanes (optima, Fisher Chemical) were used as received. Synthesis of colloidal SrTiO 3−δ and Cr 3+ -doped SrTiO 3−δ nanocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 35 publications
(58 reference statements)
5
42
0
Order By: Relevance
“…Besides a weak signal at g =1.974 attributable to Ti 3+ species (or, more descriptively, Ti 3+ −V O −Ti 4+ , i. e. an electron captured at the oxygen vacancy in the perovskite structure which is delocalized between two Ti 4+ cations), the presence of small Mn 2+ defects (signals labeled with *) is noticed with g ‐value and hyperfine constant of 2.0036 and 85 G, respectively. These impurities usually detectable in even in pure SrTiO 3 systems derive from manganese substitution for titanium ions and could explain the higher concentration of O − species in FS_300.…”
Section: Resultsmentioning
confidence: 99%
“…Besides a weak signal at g =1.974 attributable to Ti 3+ species (or, more descriptively, Ti 3+ −V O −Ti 4+ , i. e. an electron captured at the oxygen vacancy in the perovskite structure which is delocalized between two Ti 4+ cations), the presence of small Mn 2+ defects (signals labeled with *) is noticed with g ‐value and hyperfine constant of 2.0036 and 85 G, respectively. These impurities usually detectable in even in pure SrTiO 3 systems derive from manganese substitution for titanium ions and could explain the higher concentration of O − species in FS_300.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported the synthesis 29 of colloidal SrTiO 3 NCs by modied hydrothermal methods 15,17,18 that are readily suspended in non-polar solvents. Electron paramagnetic resonance (EPR) and optical spectroscopies showed that the SrTiO 3 NCs can display spectroscopic signatures that were assigned to an oxygen-related surface defect that is sensitive to the presence of hydrazine hydrate during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…These substrates were immediately used for measuring dynamic contact angle or flow coating. The colloidal undoped SrTiO 3 (STO) nanocrystals with oleic acid capping ligands were synthesized using a modified hydrothermal method (average edge dimensions of ~10 nm ± 2 nm) . The STO solutions were kindly provided to us by Kittilstved Research Group, Department of Chemistry, University of Massachusetts Amherst.…”
Section: Methodsmentioning
confidence: 99%